Effectiveness of Farmer Information Needs Assessment as Perceived by the Farmers - J Meagy; Harunor Rashid; Allen V Barker; Monirul Islam; Nazrul Islam (Journal of International Agricultural and Extension Education, 2013)
In Bangladesh, adoption of new extension program and implication is still limited. The objectives of the study were to determine and describe farmers’ perceptions on the effectiveness of Farmer Information Needs Assessment (FINA) and to explore the relationships between farmers’ characteristics and their perceptions of FINA. The study was conducted in Hajigonj, Chandpur, Bangladesh. One hundred twenty FINA-participating farmers were interviewed with a multistage, random-sampling method. An overall moderate to highly favorable perception of the FINA program was found. About half of the farmers responded with moderately favorable perceptions of FINA in providing extension services. However, less than half of the farmers responded moderately favorably in adopting recommended practices, even though more than one-third of the farmers responded with highly favorable perceptions of FINA. Seven of twelve farmer characteristics showed a significant relationship with farmer perceptions of the effectiveness of FINA: that is, middle-aged farmers were more active participants in FINA and in farming than young people; more than 60% of participants operated small farms, and they were more motivated by the FINA program than large-farm operators; farmers with moderate to high incomes participated more in FINA than did low-income farmers; and increased contact with extension personnel and increased agricultural knowledge improved farmers’ perceptions of FINA. The results allowed a conclusion that FINA, the leading problem assessment approach in agricultural extension, was effective for sustainable agricultural production. Extension departments and farmers can benefit from studying these results to identify and to solve their farming questions.
Keywords: Agricultural Extension Approach; Farmers’ Perceptions; FINA; Hajigonj; Bangladesh.